Oncogenic Role of miR-217 During Clear Cell Renal Carcinoma Progression - Zamora-Fuentes, Jose María; Hernández-Lemus, Enrique; Espinal-Enríquez, Jesús (Frontiers in Oncology, 2022)
Clear cell renal carcinoma (ccRC) comprises a set of heterogeneous, fast progressing pathologies with poor prognosis. Analyzing ccRC progression in terms of modifications at the molecular level may provide us a broader understanding of the disease paving the way for improved diagnostics and therapeutics. The role of micro-RNAs (miRs) in cancer by targeting both, oncogenes and tumor suppressor genes is widely known. Despite this knowledge, the role of specific miRs and their targets in the progression of ccRC is still unknown. To evaluate the action of miRs and their target genes during ccRC progression, here we implemented a three-step method for constructing miR-gene co-expression networks for each progression stage of ccRC, as well as for adjacent-normal renal tissue (NT). In the first step, we inferred all miR-gene co-expression interactions for each progression stage of ccRC, and for NT. Afterwards, we filtered the whole miR-gene networks by differential gene and miR expression between successive stages: stage I with non-tumor; stage II with Stage I, and so on. Finally, all miR-gene interactions whose relationships were inversely proportional (overexpressed miR and underexpressed genes and vice-versa) were kept, and removed otherwise. We found that miR-217 is differentially expressed in all contrasts, however its targets were different depending on the ccRC stage. Furthermore, target genes of miR-217 have a known role in cancer progression. For instance, in stage II network, GALNTL6 is overexpressed and it is related to cell signaling survival and proliferation. In stage III network, WNK2, a widely-known tumor suppressor is underexpressed. For stage IV network, IGF2BP2, a post-transcriptional regulator of MYC and PTEN, is overexpressed. This data-driven network approach has allowed us to discover miRs that have different targets through ccRC progression, thus providing a method for searching possible stage-dependent therapeutic targets in this and other types of cancer.